Short-term mass changes and retreat of the Ecology and Sphinx glacier system, King George Island, Antarctic Peninsula. Issue 5 (21st May 2015) - Sobota, Ireneusz; Kejna, Marek; Araźny, Andrzej
Abstract: This study investigated the mass balance, melting, near-surface ice thermal structure and meteorological conditions of the Ecology and Sphinx glacier system (ESGS), located on King George Island, Antarctic Peninsula. The study also analysed the role of climate change in glacial retreat of the ESGS in the long (1979–2012) and short term, with a particular focus on the impact on the 2012–13 mass balance of the ESGS. In 2012–13, the glaciers had a mean annual net mass balance of +17.8 cm w.e., but over the long term the glaciers have been receding in this region. The area loss of the ESGS between 1979 and 2012 amounted to 41%. This investigation of mass balance is especially important as it offers one of only a few records available on King George Island. The mean near-surface ice temperature (February to June 2012) for the Ecology and Sphinx glaciers was -0.3°C and -1.0°C at 10 m depth, respectively. From 1948–2012, the air temperature on King George Island increased by 1.2°C (0.19°C per decade).